Ruling 188: Prohibited merchant category code for Debit and Credit Card-i - Soualhi, Younes; Zakariyah, Habeebullah; Sharofiddin, Ashurov; Ishak, Muhammad Shahrul Ifwat; Hasan Saleh, Abdulmajid Obaid (Al Rajhi Bank Malaysia, 2025)
The Shariah Board of Al Rajhi Banking & Investment Corporation (Malaysia) Bhd. (“Shariah Board”) in its meeting held on 20/02/1447 H. corresponding to 14/08/2025 G. reviewed a proposal concerning “Merchant Category Codes (MCC) Classes to be Prohibited for Debit and Credit Card-i” submitted by the Bank. Previously, the Shariah Board has approved the list of prohibited MCC. The previous MCC block list lacked ownership and clear reasoning with no decision-maker and the reasoning behind the decision made was not recorded. The Bank thus would like to correct this by benchmarking against peer institutions, producing a revised block list with firm rationale and better industry alignment.